Acute therapy of stroke and reperfusion treatments - Silver, Brian (Henry Stewart Talks, 2021)
Acute ischemic stroke, Thrombolysis, CT perfusion mismatch, Thrombectomy, Devices used to treat large vessel occlusion, Imaged-Guided Patient Selection